Case report: A novel de novo variant of SCN8A in a child with benign convulsions with mild gastroenteritis - Chen, Hui; Li, Xiaoyan; Wu, Huaping; Sun, Xiaolan; Che, Yuanyuan; Zha, Jian; Wang, Ruiyan; Yu, Xiongying; Chen, Yong; Zhong, Jianmin (Frontiers in Neurology, 2022)
Benign convulsions with mild gastroenteritis (CwG) is characterized by afebrile convulsions accompanied by mild gastroenteritis, and it can be considered after central nervous system infection, hypoglycemia, electrolyte disturbance, and moderate and severe dehydration are excluded. Previous studies have suggested that genetics may be involved in CWG. Herein, we reported a novel de novo variant of SCN8A in a child with CwG. This is the first report that SCN8A may be associated with CwG. Our report may provides evidence for the genetic etiology of CwG and expands the phenotypic and genetic spectrum of SCN8A-related disorders, which previously included severe developmental and epileptic encephalopathy (DEE) phenotype, benign epilepsy phenotype, spectrum of intermediate epilepsies, and patients with cognitive and/or behavioral disturbances without epilepsy. Phenotype of CwG has a good prognosis, and it does not require long-term antiepileptic therapy. Overtreatment should be avoided clinically. However, the conclusion needs to be further defined by long-term follow-up and similar clinical reports. In spite of this, our clinical observation provides possible evidence for future studies on the relationship between SCN8A and CwG.